Effect of high hydrostatic pressure in physicochemical properties and in vitro digestibility of cornstarch by nuclear magnetic resonance relaxometry. (26th June 2019) - Okur, Ilhami; Ozel, Baris; Oztop, Mecit H.; Alpas, Hami
Abstract: Starch is the major polysaccharide consumed by human being. It is not classified as a dietary fiber as it is digestible by the enzymes present in the saliva and small intestines. However, it is possible to modify starch with thermal and nonthermal techniques. High hydrostatic pressure (HHP) is a cold pasteurization technique that has increased application in food industry with minimum effect on nutritional quality of the food products. It is hypothesized that the use of HHP could be a modification strategy for starch. In this study, effects of different HHP parameters (400 and 500 MPa) at different temperatures (20, 30, and 40°C) for 5, 15, and 30 min on in vitro digestibility and physicochemical properties of cornstarch were studied by Nuclear magnetic resonance (NMR) relaxometry. Results showed that HHP treatment increased slowly digestible starch (SDS) and rapid digestible starch (RDS) significantly with pressure and temperature ( p  < .05). In addition, it was shown that HHP treatment decreased the solubility and swelling power of the cornstarch and it is proposed that 30 min HHP treatment at 500 MPa and 40°C is the onset for cornstarch gelatinization according to NMR relaxometry results. Practical Applications: High hydrostatic pressure (HHP) is a nonthermal processing technology that is commonly used in the food industry for extending the shelf life of food products by destroying vegetative cells, enzymes, microorganisms effectively, and it can modify the starch so the aim of this study was to investigate the effects of different HHP parameters on in vitro digestibility and physicochemical properties of cornstarch by nuclear magnetic resonance relaxometry.